2022
DOI: 10.2478/hukin-2022-0047
|View full text |Cite
|
Sign up to set email alerts
|

Did the Absence of Crowd Support During the Covid-19 Pandemic Affect the Home Advantage in Brazilian Elite Soccer?

Abstract: This study aimed to investigate the impact of crowd absence due to the COVID-19 pandemic on home advantage in Series A and B of professional Brazilian male soccer. Moreover, we sought to compare the home advantage between different competitive levels. Data from 2018 to 2020 Brazilian professional soccer championships (Series A and B) were analyzed, consisting of 2280 matches. The effect of home advantage was calculated in relation to the number of points won, the number of wins, goals scored and goals conceded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…We found that matches with crowds present (3025 matches in 2012–2019 seasons and 538 matches in 2021 and 2022 seasons) presented a higher HA than matches without crowd support (380 matches in the 2020 season, and 219 matches in the 2021 season). Previous studies showed similar results for soccer leagues in Brazil ( Ribeiro et al, 2022 ), Germany ( Santana et al, 2021 ; Sánchez & Lavín, 2020 ), and Spain ( Sánchez & Lavín, 2020 ). During 11 years of the Brazilian Soccer League the number of goals scored was significantly higher for home teams compared to away teams; however, teams who played away made more goals increases when the stadiums were empty of crowds than when crowds were present.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…We found that matches with crowds present (3025 matches in 2012–2019 seasons and 538 matches in 2021 and 2022 seasons) presented a higher HA than matches without crowd support (380 matches in the 2020 season, and 219 matches in the 2021 season). Previous studies showed similar results for soccer leagues in Brazil ( Ribeiro et al, 2022 ), Germany ( Santana et al, 2021 ; Sánchez & Lavín, 2020 ), and Spain ( Sánchez & Lavín, 2020 ). During 11 years of the Brazilian Soccer League the number of goals scored was significantly higher for home teams compared to away teams; however, teams who played away made more goals increases when the stadiums were empty of crowds than when crowds were present.…”
Section: Discussionsupporting
confidence: 65%
“…In Brazil, Ribeiro et al (2022) found a reduction in the HA for First Division of the Brazilian Soccer League without crowd support in soccer stadiums. These authors used a different formula to determine the HA ( Matos et al, 2020 ), in which the results could present positive or negative values, with a higher score indicating a greater effect of the HA.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, shots on goal (accuracy) decreased for the home team without a crowd in the European soccer matches, and players' high-intensity running activities did not change but total distance and high-speed running distance decreased during the entire match (McCarrick et al, 2021;Rampinini et al, 2021;Wunderlich et al, 2021). Moreover, there was a reduction in HA for Serie A, but no change in HA for Serie B was reported in Brazilian Elite Soccer (Ribeiro et al, 2022). However, to the best of our knowledge, there is no investigation about the direct effects of absent crowds on match performance in the Asian football league.…”
Section: Introductionmentioning
confidence: 94%